Artificial incubation of eggs of Lima gecko (Phyllodactylus sentosus) (Reptilia, Geckonidae) kept in captivity - Sánchez M., Vanessa (2022)
Phyllodactylus sentosus is an endemic saurian from Peru, which is categorized by the IUCN Red List and Peruvian legislation (DS N.° 004-2014-MINAGRI) as Critically Endangered. The aim of this study was to establish artificial incubation parameters in the species to increase the knowledge of its maintenance in captivity and to contribute to conservation programmes. Five eggs were artificially incubated from the clutches of three free-living gravid female individuals of P. sentosus kept in captivity. Incubation periods between 85 to 93 days were recorded, at an average temperature of 26 °C and relative humidity between 76 to 80%.